2010
DOI: 10.1029/2009ja014662
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship of Joule heating and nitric oxide radiative cooling in the thermosphere

Abstract: [1] During geomagnetic storms Joule heating dissipation is the dominant form of magnetospheric energy input that is responsible for many chemical and dynamical variations in the thermosphere. One such thermospheric variation is the dramatic increase of thermospheric temperature and nitric oxide (NO) density and thus radiative emission by NO. This paper gives for the first time a quantitative assessment of the relationship between global Joule heating power and global NO radiative cooling power. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 29 publications
11
110
0
Order By: Relevance
“…It is thought that the accelerated cooling is the result of extra NO that is produced as a by-product of both the enhanced auroral particle precipitation and the global heating. The experimental evidence documented by Barth et al [2009], Barth [2010], and Lu et al [2010] support this hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…It is thought that the accelerated cooling is the result of extra NO that is produced as a by-product of both the enhanced auroral particle precipitation and the global heating. The experimental evidence documented by Barth et al [2009], Barth [2010], and Lu et al [2010] support this hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…This result, even though the authors did not separate ICME and CIR events, supports the above suggestion of efficient generation of disturbance dynamos during HSS events. The physical mechanism is the extended Alfvénic wave trains within the HSSs and explains the VTEC Lu et al (2010), Joule heating/dissipation is shown to be responsible for the enhanced thermospheric radiative emission by NO during geomagnetic disturbances. On the other hand, the disturbance dynamo mechanism does not account for the fast response (within ∼1 h) of VTEC enhancements in low-to middle-latitudes noted during CIR/HSS events .…”
Section: Discussionmentioning
confidence: 99%
“…These events were attributed to additional energy input due to geomagnetic activity (Mlynczak et al, 2010b). Lu et al (2010) have shown that Joule heating dissipation is responsible for thermospheric temperature and NO density increases and thus radiative emission by NO in the thermosphere during geomagnetic storms. Geomagnetic/auroral activity in general is suggested to cause most of the thermospheric radiated power variability (Solomon et al, 1999;Marsh et al, 2004;Mlynczak et al, 2010b;.…”
mentioning
confidence: 99%
“…An evaluation of the TIE-GCM with other models can be found in the work of Shim et al [this volume]. The TIE-GCM, TIME-GCM, and CMIT have been used extensively for ionosphere and thermosphere studies, including studies for geomagnetic storms [e.g., Burns et al, 1992Burns et al, , 1995aBurns et al, , 1995bBurns et al, , 2008Crowley et al, 2010;Wang et al, 2008Wang et al, , 2010Lei et al, 2010], solar flares [e.g., Qian et al, 2010bQian et al, , 2012, tides [e.g., Hagan et al, 2009;Pedatella et al, 2011], recent solar minimum [e.g., Solomon et al, 2010Solomon et al, , 2011, effects of sudden stratospheric warming [e.g., Liu et al, 2010b], equatorial ionosphere [e.g., Fang et al, 2008], IR cooling [e.g., Lu et al, 2010], effect of high-speed solar wind [e.g., Qian et al, 2010a;Wang et al, 2011;Burns et al, 2012;Solomon et al, 2012], data assimilation [e.g., Lee et al, 2012;Matsuo et al, Assimilative thermospheric mass density specification using ensemble Kalman filter, submitted to Journal of Geophysical Research, 2012;], and long-term changes [e.g., Cnossen and Richmond, 2008;Qian et al, 2009b].…”
Section: Some Model Validation Examplesmentioning
confidence: 99%